Case report: Usefulness of a picosecond Alexandrite laser therapy on atypical henna-induced Riehl's melanosis inferred from immunohistochemical analyses - Kishimoto, Mami; Iwayama, Takanori; Horita, Nobuyuki; Fukumoto, Takeshi (Frontiers in Medicine, 2024)
Riehl's melanosis is a pigmented dermatitis that manifests as brown-gray facial pigmentation with pigment incontinence and infiltration of cells in the upper dermis. The associated inflammation is induced by a variety of products such as drugs and cosmetics. Henna, commonly referred to as a hypoallergenic cosmetic, has been reported to cause Riehl's melanosis in some cases. Although skin depigmenting agents have been occasionally used, satisfactory results have not been obtained and no established therapeutic strategies exist to treat Riehl's melanosis. Meanwhile, picosecond lasers effectively treat other hyperpigmentation disorders. In this study, we report safe and effective treatment of henna induced-atypical Riehl's melanosis using a 755-nm picosecond Alexandrite laser. Immunohistochemical analyses revealed a potential role of CD8-positive lymphocytes in henna-induced inflammation and hyperpigmentation of the basal layer, and a role of melanophages in the pigmented dermis of Riehl's melanosis.